2020
DOI: 10.1016/j.jdsr.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor is related to stress and chewing in saliva and salivary glands

Abstract: SummaryChewing is one of the most important orofacial functions. During this process, food is reduced in size, while saliva moistens the food and binds it into a bolus that can be easily swallowed. Characteristics of the oral system, including the number of teeth, bite force, and salivary flow, influence the masticatory process. In addition, salivary glands produce several cell growth factors and play an important role in human health. The nerve growth factor (NGF) family consists of NGF, brain-derived neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 124 publications
0
10
0
3
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) and its related pathways may play a certain role in this process (Huang et al, 2021 ). BDNF is one of the most widely studied neurotrophic factors, produced by nervous system and dominant target organs [such as muscle, dental pulp, and salivary gland (Saruta et al, 2020 )]. It is mainly expressed in the hippocampus, cerebral cortex and other cognition-related brain regions, assisting development and repairing of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and its related pathways may play a certain role in this process (Huang et al, 2021 ). BDNF is one of the most widely studied neurotrophic factors, produced by nervous system and dominant target organs [such as muscle, dental pulp, and salivary gland (Saruta et al, 2020 )]. It is mainly expressed in the hippocampus, cerebral cortex and other cognition-related brain regions, assisting development and repairing of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is essential to preserve oral health as alterations in the salivary gland function could affect oral tissue integrity [26]. Function of the salivary glands is essentially controlled by the autonomic nervous system, so it is directly affected on exposure to stresses [26] . BDNF is among the stress markers in saliva that have been identi ed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anorexic behavior reduces the number of meals/chewing activity in the oral cavity, decreases salivary output, and alters saliva composition and sensory perceptions [ 1 , 8 , 9 ]. Recent research on animal models has demonstrated that chewing could help attenuate the stress-induced neurophysiological response [ 10 , 11 ]. This effect might be mediated, at least in part, by saliva that besides its lubricative properties helping food bolus transformation, is known to be part of a neuroendocrine axis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%